Enhancing Sustainable Development Efficiency Through a Single Smart City Platform: A Cost-Benefit Policy Perspective from Indonesia - Amnesti, Sheila Kusuma Wardani; Adityo, Rayno Dwi; Zulaichah, Siti; Hariz, Hajar Salamah Salsabila; AllahRakha, Naeem (Volksgeist: Jurnal Ilmu Hukum dan Konstitusi, 2025)
The issue of "application fatigue" among government agencies has led to a reluctance among user to download or engage with existing applications. The intent behind these applications is to digitalize government functions, particularly in enhancing public services. This article explores the application of cost-benefit analysis (CBA) regarding the development of smart city policies in Indonesia. Historically, smart city initiatives have often translated into the creation of new applications by both central and regional government entities. This study employs normative legal research, utilizing both a statutory and cost-benefit analysis approach to investigate smart city implementation. The findings that the current conditions for smart city development in Indonesia are regressing, primarily due to lack of central government regulations that serve as guidelines for these initiatives. The involvement of stakeholders is examined based on their authority and interests, which significantly influence the implementation of the single smart city platform. Furthermore, the cost-benefit analysis demonstrates the importance of establishing and implementing this single smart city platform as a means to enhance decision-making efficiency within government agencies. It is hoped that this article will serve as a recommendation for policymakers to conduct through analysis prior to program development to ensure feasibility and effectiveness.